Lifetime comparison of Y-TZP/porcelain crowns under different loading conditions - Corazza, P. H. [UNESP]; Duan, Y.; Kimpara, E. T. [UNESP]; Griggs, J. A.; Della Bona, A. (Elsevier B.V., 2015)
Objectives: To compare the lifetime of Y-TZP/porcelain crowns under three different load conditions using step-stress accelerated lifetime testing.Methods: The Y-TZP frameworks were milled using CAD/CAM, veneered with a porcelain and cemented onto dentine analogue dies. Specimens were divided according to the occlusal load condition (n = 20): central fossa load (CFL), cusp tip load (CTL) and sliding contact (SC). For CFL and CTL, the cyclic load was applied parallel to the long axis of the preparation using a ceramic piston. For SC, the axial load was associated to 1 mm lateral displacement at the disto-lingual cusp. Different stress profiles were used. Failures were detected with an acoustic system. A Weibull distribution (95% confidence boundary) was used to analyse the data, and fractographic principles were used to evaluate fractured specimens.Results: The acoustic monitor was able to detect the initial crack. The probability of failure (at 300 N load and 200,000 cycles) was statistically greater for CTL (0.63; 0.44-0.81) compared to CFL (0.23; 0.12-0.43). The Weibull modulus of CFL (2.1; 1.5-3.6) was greater than for SC (0.7; 0.5-1.2), with no difference in the lifetime. All specimens failed by chipping, which originated predominantly at the contact (66.7%) on CTL, and in the bulk of the porcelain on CFL (100%) and SC (80%).Conclusions: Contact at the cusp tip is more harmful than at the central fossa. Data from sliding contact are less consistent than from axial contacts, but more clinically relevant.Clinical significance: The loading condition of Y-TZP/porcelain crowns can influence on the probability of failure and failure mode. The contact at the cusp tip is more harmful than at the central fossa, where the stress is better distributed. Sliding contact is a better simulator of the chewing cycle compared to axial contacts. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Dental occlusion; Ceramics; Materials failure analysis; Stress, Mechanical; Sound waves; Prosthodontics